PENGARUH LATIHAN STANDING DUMBBELL TRICEPS EXTENSION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PUTRI KEPELATIHAN A TAHUN ANGKATAN 2014 UNIVERSITAS RIAU - Welis Farida Ayu; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is whether there is effect of standing dumbbell triceps extension exercise toward the strength of arms and shoulder muscle of 2014 Female A Students of Riau University which is still low, it could be seen from the observation of some of the branch sports which used the power of arms and shoulders, for example handball, gymnastics and shot put, among the three of these, it could be seen that their power was still low so they did not reach the target that had been set. This research is experimental research, the population in this research is the female student A of 2014 University of Riau, the sample in this research is the whole population which totals 8 students. The technique of collecting data is taken from the pre-test and post-test. The instrument used in this research is expanding dynamometer which purposes to measure the strength. The independent variable is the standing triceps dumbbell extension exercise (x), while the dependent variable is the strength of the arm and shoulder muscles (y). After that, the data is processed statistically to test the normality with Liliefors test at significance level 0,05α. The hypothesis is there is effect of standing dumbbell triceps extension exercise toward the strength of arm and shoulder muscles. Based on t test analysis, Tresult is 4.17 and Ttable is 1,895, which means Tresult > Ttable. It can be concluded that Ha is accepted. The result of the research concludes that there is a significant effect of standing dumbbell triceps extension exercise toward the strength of arms and shoulder muscle of Female A Students in the year of 2014 in Riau University.Key Words: Standing dumbbell Tricep Extension Exercise, the strength of shoulder and arm muscle